2023
DOI: 10.32607/actanaturae.11890
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Profiling in Patients with Pemphigus Vulgaris

Abstract: Pemphigus vulgaris is a severe, socially significant autoimmune disease associated with autoantibodies to the desmoglein 3 antigen. The disease affects all age groups, beginning at 18 years of age; the mortality rate of pemphigus can reach as high as 50%, depending on a patients age and a number of other factors. There is no highly selective or personalized therapy for pemphigus vulgaris at the moment. One of the well-known therapeutic approaches to the disease is to use rituximab, an anti-CD20 antibody that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Remarkably, the disease severity of PV has been correlated with the abundance of serum DSG1/3-specific autoantibody. The well-characterized antigenic specificity for DSG1/3 has allowed researchers to isolate these pathogenic B cells from the peripheral blood of PV patients, thus elucidating their distinctive transcriptomic and phenotypic profiles ( 51 53 ). Detection of DSG1/3-specific B cells in PV patients demonstrated that DSG1/3-specific memory B cells also correlate with disease severity ( 51 , 52 ).…”
Section: Role Of B Cells In Various Inflammatory Skin Diseasesmentioning
confidence: 99%
“…Remarkably, the disease severity of PV has been correlated with the abundance of serum DSG1/3-specific autoantibody. The well-characterized antigenic specificity for DSG1/3 has allowed researchers to isolate these pathogenic B cells from the peripheral blood of PV patients, thus elucidating their distinctive transcriptomic and phenotypic profiles ( 51 53 ). Detection of DSG1/3-specific B cells in PV patients demonstrated that DSG1/3-specific memory B cells also correlate with disease severity ( 51 , 52 ).…”
Section: Role Of B Cells In Various Inflammatory Skin Diseasesmentioning
confidence: 99%